Peran Influencer Dalam Strategi Promosi Era Digital Disruption Terhadap Perilaku Konsumen : Studi Kasus Followers Instagram Fadil Jaidi - Fernandes, Deonri; Azhar, Andi (Jurnal Inovasi Bisnis Manajemen dan Akuntansi, 2025)
This article discusses the role of influencers in promotional strategies during the era of digital disruption and their impact on consumer behavior, focusing on Instagram follower Fadil Jaidi. In the context of modern marketing, influencers have become a key element capable of influencing purchasing decisions through the content they present. This research employs a case study method to analyze how Fadil Jaidi, as an influencer, utilizes the Instagram platform to build relationships with his audience and promote products. The findings indicate that the engagement and trust established by influencers significantly affect consumer behavior, including increased brand awareness and purchase intention. These insights provide valuable guidance for marketers in designing effective promotional strategies amid the changing market dynamics driven by digital technology